Occurance of morphological deformities in mud crab Scylla serrata exposed to antibiotics during the larval stage - Pates, Gaudioso Saloma (Miagao, Iloilo University of the Philippines Visayas, 2012)
The effect of antibiotics on the external deformities, growth and survival of Scylla serrate larvae and juveniles were determined in three separate experiment. Newly-hatched soeae were exposed to oxytetracycline (0, 3.0, 6.0, 9.0, 12.0 ppm) and Purazolidone (0, 0.5, 1.5, 2.0 ppm) in the first and second experiments, respectively, until the late megalopa stage. The crablets (0.89-1.10 internal carpace width) produced from each replicate were further grown in concrete nursery tanks (10 m2) for one month. The treatments which produced best results for each antibiotic were simultaneously run in the third experiment. Morphological deformities observed in zoea 5 were bent dorsal, rostral and furcal spines. There was no significant difference (P>0.5) on the deformities of zoea 5 in two concentrations of oxytetracycline (3.0 and 6.0 ppm) and furazolidone (0.5 and 1.0 ppm). Moreover, survival to megalopa was attained only in these treatments (oxytetracycline and furazolidone). Significantly (P<0.05) higher survival and higher growth index were attained in lower concentrations of oxytetracycline (3.0 ppm) and furazolidone (0.5 ppm). Morphological deformities observed in juveniles were fused frontal and lateral spines, asymmetrical and depressed tip of abdominal flap and gap between sternites. High percentage occurrence of deformities was observed in the 6.0 ppm oxytetracycline and 1.0 ppm furazolidone in the first and third experiments, respectively. No deformities were observed in both treatments in the second experiment. There was no significant difference (P>0.05) observed in the survival of juveniles in both treatments of oxytetracycline and furazolidone. However, growth rates were significantly (P<0.05) faster in lower concentrations of the two antibiotics. These results suggest that mud crab S. serrate larvae can be best reared in 3.0 ppm oxytetracycline or 0.5 ppmfurazolidone. However, development of hatchery techniques to minimize or eliminate the use of antibiotics to prevent probable harm to the organisms in the wild must also be addressed.
Thesis (M.S. Fisheries - Fisheries Biology) -- Miagao, Iloilo : University of the Philippines Visayas, February 2012.
Keywords: mud crab; Scylla serrata; antibiotics